Niobes antiquity, modernity, critical theory - Telò, Mario 1977-; Benjamin, Andrew E. 1952- (Classical memories/modern identities, 2024)
"Reconstructing the dialogue of Phillis Wheatley, G.W.F. Hegel, Walter Benjamin, and Aby Warburg with Niobe as she appears in Aeschylus, Sophocles, Ovid, and the visual arts, contributors imagine new ways of connecting the classical tradition and ancient tragic discourse with crises and political questions relating to gender, race, and social justice."